2022
DOI: 10.1038/s41598-022-08630-1
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial reverse remodeling improves risk stratification in patients with heart failure with recovered ejection fraction

Abstract: We aimed to investigate the relationship between left atrial (LA) reverse remodeling and prognosis of heart failure (HF) with recovered ejection fraction (EF) (HFrecEF). Among 1,246 patients with acute heart failure enrolled in the prospective longitudinal follow-up study, 397 patients with HF with mildly-reduced EF and with reduced EF at discharge were analyzed. Echocardiography was performed during the index hospitalization and at the 6-month follow-up after discharge. They were divided into non-HFrecEF (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…26 The researchers observed that left atrial reverse remodelling was associated with a lower cumulative 6-month incidence of a composite of all-cause death or hospitalization for heart failure in patients with HFrecEF but not with non-HFrecEF, suggesting that the effect of left atrial reverse remodelling on clinical outcome was based on the recovery of LV systolic function. 26 In this study, we found that HFpEF patients with left atrial reverse remodelling had improved clinical outcomes, manifested by lower risks of hospitalization for worsening heart failure and the composite endpoint, which were consistent with previously published trials. Additionally, patients with improved left atrium did not show a statistical benefit in reducing mortality, which may be because of the relatively small sample size and lower rates of mortality observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The researchers observed that left atrial reverse remodelling was associated with a lower cumulative 6-month incidence of a composite of all-cause death or hospitalization for heart failure in patients with HFrecEF but not with non-HFrecEF, suggesting that the effect of left atrial reverse remodelling on clinical outcome was based on the recovery of LV systolic function. 26 In this study, we found that HFpEF patients with left atrial reverse remodelling had improved clinical outcomes, manifested by lower risks of hospitalization for worsening heart failure and the composite endpoint, which were consistent with previously published trials. Additionally, patients with improved left atrium did not show a statistical benefit in reducing mortality, which may be because of the relatively small sample size and lower rates of mortality observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent sub-study analysis, the investigators discovered that spironolactone had no significant effects on the improvement of left atrial and LV structure, whereas an overall reduction in left volume was associated with lower risks of occurrence of cardiovascular death, heart failure-related hospitalization, and aborted cardiac arrest 25 . Shiba et al conducted a prospective longitudinal study to investigate the relationship between left atrial reverse remodelling and the prognosis in heart failure with recovered ejection fraction (HFrecEF) 26 . The researchers observed that left atrial reverse remodelling was associated with a lower cumulative 6-month incidence of a composite of all-cause death or hospitalization for heart failure in patients with HFrecEF but not with non-HFrecEF, suggesting that the effect of left atrial reverse remodelling on clinical outcome was based on the recovery of LV systolic function 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective longitudinal follow‐up study from Japan indicated that LARR was associated with a lower cumulative 6‐month incidence of composite of all‐cause death or hospitalization for HF, and the effect was based on LV reverse remodeling. 26 The multicenter automatic defibrillator implantation trial with cardiac resynchronization therapy trial demonstrated that the majority of patients with LV dysfunction and mild HF symptoms selected for cardiac resynchronization therapy–defibrillator therapy experienced a ≥20% reduction in LA volume, whereas the implanted cardiac device–only group had a significantly lower LA response at 1 year (median left atrial volume reduction: 29% [20%–36%] versus 10% [5%–14%]). 27 Consequently, patients who showed a favorable LA response to cardiac resynchronization therapy–defibrillator therapy experienced lower risks of atrial tachycardia, HF events, and death.…”
Section: Discussionmentioning
confidence: 99%